2011
DOI: 10.2217/pgs.11.46
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Male Schizophrenia: Influence of Antipsychotic Drugs, Prolactin and Polymorphisms of the Dopamine D2 Receptor Genes

Abstract: This is the first evidence indicating that antipsychotic drug treatment in men is associated with a variant in the DRD2 gene in which the -141C Del allele might be a protective factor. While this may, in part, be mediated by effects on prolactin, other factors are likely to contribute to the greater sexual dysfunction in patients receiving typical antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 59 publications
3
40
2
Order By: Relevance
“…It has also been hypothesized that sexual dysfunction in men receiving selective 5-HT reuptake inhibitors may be dependent on the variability of the DRD2 gene [7]. Furthermore, Chinese authors reported that sexual dysfunction is found more often in patients with schizophrenia who have a higher frequency of the Ins allele of the DRD2-141C Ins/Del polymorphism [24]. In our investigation there was no association between the DRD2 C313T polymorphism and the sexual scale of AMS.…”
Section: Discussioncontrasting
confidence: 48%
“…It has also been hypothesized that sexual dysfunction in men receiving selective 5-HT reuptake inhibitors may be dependent on the variability of the DRD2 gene [7]. Furthermore, Chinese authors reported that sexual dysfunction is found more often in patients with schizophrenia who have a higher frequency of the Ins allele of the DRD2-141C Ins/Del polymorphism [24]. In our investigation there was no association between the DRD2 C313T polymorphism and the sexual scale of AMS.…”
Section: Discussioncontrasting
confidence: 48%
“…reported the importance of DRD2 − 141 C Ins/Del polymorphism in antipsychotic (any one of the five antipsychotics) response and associated adverse effects in Chinese population (thirty patients received risperidone) and shown a significant association. [15] Similarly, other studies reported the role of serotonin receptor polymorphism 5HTR2C (−759 C>T) in antipsychotic-induced weight gain, prolactin increase, and EPSs. [161718] Due to limited data and involvement of various antipsychotics, none of the studies have established genetic polymorphisms as biomarkers in the clinical setting.…”
Section: Introductionmentioning
confidence: 84%
“…They have reported the association of DRD2 (Taq1A; −141 C Ins/Del) gene polymorphism with elevated prolactin levels in Chinese patients on antipsychotic medication. [15] A recent study by Sukasem et al . reported the DRD2 (Taq1A) variants association with elevated prolactin levels, and Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sexual side effects are most prevalent in those APs that have the most pronounced D2 antagonism, mainly typical APs and risperidone (141). One study suggests that erectile dysfunction and other sexual dysfunctions in men, as a side effect of AP treatment, is linked to a polymorphism of the dopamine D2 receptor ((141C Ins/Del [rs179973]) (142). A case study by Mesa et al suggested the addition of a D2 agonist could eliminate the sexual side effects caused by AP use (143).…”
Section: Pharmacodynamicsmentioning
confidence: 99%